O bloqueio de PI3Kγ atenua a mucosite intestinal induzida por irinotecano em camudongos - Cajado, Aurilene Gomes (2024)
Introduction: Mucositis is a common toxicity in cancer treatment involving irinotecan (IRI). Patients with mucositis have double the risk of infections, increasing four-fold the risk of death. Phosphatidylinositol-3-kinase gamma (PI3Kγ) is widely expressed in leukocytes, and its inhibition has been considered a promising therapeutic strategy for the control of inflammatory and autoimmune disorders. Objective: To evaluate the role of PI3Kγ in an irinotecan-induced intestinal mucositis model and to test the potential synergistic antitumor effect between irinotecan and AS-605240, a selective PI3Kγ inhibitor. Methods: Male C57BL/6 mice (20-22g, n=6-9/group) received a vehicle, IRI (120 mg/kg, one injection/day/four days, i.p.) alone, or combined with AS-605240 (10 mg/kg, p.o.). On the seventh day after the first IRI dose, the severity of diarrhea was determined. After euthanasia, the ileum was collected for morphometry, gene expression analysis of Tlr2, 4, and 9, Aim2, as well as targets characterizing the T cell polarization profile such as Tgfb, Cxcl1, Il12b, Ifng, Il33, and Il4. Cytokine levels (IL1-β and IL-6), and the expression of pAKT, FOXP3, and F4/80 by immunofluorescence were also assessed. Additionally, malondialdehyde (MDA), glutathione (NP-SH), myeloperoxidase (MPO) levels, and the count of goblet cells stained with Alcian Blue and PAS were measured. To evaluate the synergistic effect between irinotecan and AS605240, the antitumor effect (Mc-38 cells, 1x10^6 cells, in the axillary region) was assessed after seven days of treatment. Study approval protocol: CEUA N°5132240718. Results: PI3Kγ inhibition attenuated morphometric changes by improving the villus/crypt ratio and reducing histopathological scores (1[1-2]) vs. the IRI group (2[1- 2]). Additionally, there was modulation of the inflammatory response by reducing the expression of Tlr 2, 4, 9, and phosphorylated AKT protein in the AS-605240 treated group. The involvement of the Treg response in the IRI group was evidenced by increased Tgfb (up to 65-fold) and FOXP3 (4% fluorescence area) compared to the vehicle group. Th17 response targets also increased in the IRI group, including IL-6 (57.72±8.4 vs 39.09±3.8) and Cxcl1 (9.8-fold), promoting increased neutrophil migration (4242±1187), MDA production (12.46±1.23), and reduced NP-SH (421.4±44.13) compared to the vehicle group (876.4±81; 5.057±0.97; 568.3±24.4, respectively). Notably, AS-605240 treatment reversed these parameters by reducing Tgfb (22.3±4.1), FOXP3 (2.17%), IL-6 (23.6±3.1), Cxcl1 (1.2±0.8), MPO (1436±268), MDA (6.4±1.0), and maintaining NP-SH levels (563.6±38.89). Furthermore, AS605240 decreased F4/80 (2.18% fluorescence area) and IL-1β levels (average 30.25 pg/mg) compared to IRI. However, Il12b and Ifng expression did not change between these groups. Finally, we found that AS-605240 did not alter Il33 levels (49.9±9.9) but increased Il4 (4.5±1.3) vs. the IRI group (Il33: 44.9±7.7; Il4: 0.7±0.1). Additionally, AS-605240 increased the number of acidic goblet cells vs. the IRI group (10.5±4.6 vs. 8.7±0.6) and neutral cells (14.3±0.6 vs. 8.3±0.7), suggesting the involvement of Th2 cells in intestinal mucus production. Together, these changes promoted by PI3Kγ inhibition contributed to attenuating diarrhea severity vs. the IRI group (AS-605240: 1[1-2] vs. IRI: 2[1-3]). Finally, the pharmacological combination of AS-605240 with IRI did not potentiate tumor growth inhibition in the in vivo assay. Conclusion: PI3Kγ inhibition attenuated intestinal damage by modulating the inflammatory response towards a Th2 lymphocyte profile, reducing diarrhea severity, and contributing to increased goblet cell numbers and intestinal protection without compromising the antineoplastic effect of irinotecan.